DEVELOPMENT OF A NOVEL SEISMIC FORCE RESISTING SYSTEM: CONTROLLED ROCKING MASONRY WALLS WITH ENERGY DISSIPATION ACCESSIBLE CONSTRUCTED ATOP A STEEL BASE - East, Matthew (My University, 2022)
Conventional seismic design practices for reinforced masonry shear walls rely on ductility within the system, typically in the form of yielding of bonded reinforcement within the wall. While this is effective at dissipating energy, it comes at the expense of signi ficant damage in the plastic hinge region, as well as substantial residual deformations. This results in costly repairs being required following a seismic event, and in some cases demolition. Controlled rocking systems have been garnering considerable attention as a design approach that can mitigate these shortcomings. In a controlled rocking wall system, the wall is permitted to uplift from the foundation, reducing the lateral stiffness of the wall and producing a nonlinear response without relying on ductility within the wall. This response is typically controlled with the use of unbonded post-tensioning (PT) tendons within the wall to provide a restoring force to the system and eliminate residual drifts. These systems are considered favorable for resilient design as the repair costs and the corresponding service shutdowns are minimized. In application to masonry systems speci fically, the PT tendons impose additional compressive stresses on the rocking toes, resulting in damage in these regions of the wall. In addition to this, the construction process of a masonry wall with unbonded PT can have challenging detailing considerations. Meanwhile, previous studies have also indicated that controlled rocking masonry systems (CRMWs) have relatively low inherent damping. Recent studies have shown promising results by testing CRMWs that rely on gravity loading for a self-centering response, omitting PT, and introducing energy dissipation inside the walls. However, as the devices are within the wall, they are difficult or impossible to repair if needed following a seismic event. In this respect, the current thesis begins with an investigation of an externally mounted, replaceable energy dissipation device in the form of a flexural yielding cantilever arm. Experimental tests of the devices are analyzed, and the experimental results are used together with numerical modelling of the devices to develop design equations. Following this, a numerical study is conducted to evaluate the effectiveness of the proposed flexural arm devices within a new CRMW system. A new damage index for reinforced masonry walls is introduced and then applied to compare the effectiveness of innovative CRMW design alternatives. This work ultimately proposes a system that has Energy dissipation Accessible, constructed atop a Steel rocking base (EASt-CRMW), which has a desirable self-centering response relying on gravity loads, with the flexural arms adding supplemental energy dissipation to the system. Building on these developments, two large-scale experimental studies on EASt-CRMWs are presented. The first study reports the results of six EASt-CRMWs with various parameters. The results display a highly favorable hysteretic response, able to withstand drifts as high as 5% with negligible damage and residual drifts of less than 0.1%. This study then proposes two procedures to predict the monotonic force-displacement response of the EASt-CRMW system. The second experimental study investigates the performance of two additional EASt-CRMWs in which the flexural yielding energy dissipation devices were replaced and the walls retested, showing that the system can produce nearly identical results upon retesting. The study then validates the previously discussed numerical modelling approach for the further application of EASt-CRMWs, indicating that the model developed is indeed capable of capturing the actual response of the system and that the damage index accurately predicts the location and severity of damage within EASt-CRMWs.